Society’s Construction of Masculinity and Its Toxicity Among Selected Male College Students: Lived Experiences: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This descriptive research was conducted to determine how Society’s Construction of Masculinity and its toxicity affect selected male college students at Bestlink College of the Philippines. Questions were formulated to guide this study. The study population consists of any college department's 1st to 4th year. Through the process of simple random sampling and snowball sampling, a total number of 12 students were recommended and selected to participate in the study. The major instrument used to gather the needed data was a set of survey questionnaires, and the researchers conducted an interview. The data gathered was analyzed through the use of percentages and weighted mean. This was the basis to find out the real problem behind the toxic stereotypes about men’s masculinity and how the researchers can help to educate people and raise awareness through this study.  Studying Society’s Construction of Masculinity and its toxicity among selected male college students has a purpose in giving information and a moral lesson to the people, especially the youth. It is important because it will serve as an enlightenment for young men nowadays to help them to be more aware of how Toxic Masculinity can affect one's Mental Health as well as their social relationships and how they can cope with it in the future.